'A very human business'—Transnational networking initiatives and domestic climate action. (January 2019) - Perkins, Richard; Nachmany, Michal
Highlights: Past work largely ignored social and emotional roles of networking initiatives. Analyse experience of parliamentarians enrolled in GLOBE International. Involvement in networking initiative associated with political learning. Evidence that participation led to solidarity, emotional energy and inspiration. Highlight importance of taking account of collective and emotional aspects. Abstract: The past two decades have witnessed a proliferation of transnational networking initiatives aimed at addressing climate change. Previous work has suggested that these initiatives largely achieve their governance functions by fostering learning and resource acquisition. Our particular contribution seeks to advance current understanding of networking initiatives by suggesting that they may additionally perform social and emotional roles which galvanise, energise and motivate actors to pursue actions which advance domestic climate goals. To illustrate our argument, we examine GLOBE International, an inter-parliamentary institution focused on supporting the development of domestic legislation around sustainable development. Based on semi-structured interviews with legislators, we provide evidence that GLOBE functions as a network for learning, and particularly political learning. Yet participation in the group setting of the initiative's summits has additionally given rise to feelings of unity, emotional energy and inspiration. We conclude by discussing the implications of our findings, which paint a richer, more complex picture of transnational climate governance than previously acknowledged in the literature.